THE INFLUENCE OF THE GOVERNMENT'S ROLE IN STRENGTHENING THE BETWEEN BUDGET ALLOCATION TOWARDS SPORTS ACHIEVEMENT IN THE BINJAI CITY'S YOUTH AND SPORTS DEPARTMENT - Muhammad Sofian Siregar; Mesra B (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The purpose of this research is to determine and analyze the influence of the government's role in strengthening budget allocations on sports performance in the Binja City Youth and Sports Department. The type of research is associative quantitative. The population in this study were all employees with ASN and Honorary status at the Binjai City Youth and Sports Service, totaling 90 employees. The sampling technique in this study was a saturated sample where all populations were sampled. The data collection technique that was carried out was by distributing questionnaires. Data analysis in this study used the PLS Structural Equation Model with the Smart PLS 3.0 Application Program. The results of this study indicate that the budget allocation has no significant effect on sports achievement based on the results of the T-statistic value of 0.909 > 1.96 with a P-Value of 0.366 > 0.05. In the Moderated Regression Analysis (MRA) test, a T-Statistic value of 0.502 > 1.96 was obtained with a P-Value of 0.617 > 0.05, which means that the moderating variable, namely the role of the government, is not able to significantly strengthen the influence of budget allocations on sports achievements at the Youth Service and Binjai City Sports.